THE SCIENCE BEHIND MEDICAL MARIJUANA AND RESEARCH CHALLENGES - Knezevic, Nebojsa Nick; Pirvulescu, Iulia (HEALTH CARE, 2021)
Endocannabinoids are lipid-based retrograde neurotransmitters that bind to cannabinoid receptors, two of which are currently described: CB1 and CB2. The two main active components of cannabis are tetrahydrocannabinol (THC) and cannabidiol (CBD), have differing binding affinities to the receptors, allowing them to mediate different systemic effects as well as modulate each other’s effects. Due to these varied properties, the therapeutic effect of marijuana is directly correlated with the THC:CBD ratio in a particular formulation. Current FDA-approved synthetic and cannabis-derived products are indicated for the treatment of seizure disorders, chemotherapy-induced nausea, and anorexia in AIDS patients. For the treatment of chronic neuropathic pain and cancer pain, research has shown a low-to-moderate quality evidence of cannabinoids’ benefit, but greatly promising in providing alternatives to opioids. Challenges in medical research on cannabis remain, particularly in terms of inconsistent chemical composition and sourcing, small sample sizes, poor controls, and short duration of trials. Major medical institutions call for rigorous research to further investigate marijuana safety and efficacy.